GENDER STEREOTYPES AND LABOUR SEGREGATION IN DENTAL OFFICES - Samkharadze, Sopio; Alkhanishvili, Zurab; Lursmanashvili, Landa; Gvasalia, Nino (European Scientific Journal, ESJ, 2016)
Ensuring the gender equality is one of the most important element for the formation of developed society. The aim of the research represented the study of factors acting on the processes of the gender socialization in dentists, the estimation of self-perception or denial of gender inequality by dentists, the manifestation, description and analysis of gender stereotypes and the study of gender characteristics, such as the gender identity, mood and behavior of involved subjects. The number of respondents were 179 dentist. There were used both qualitative and quantitative methods of research. The research confirms that the gender stereotypes, existent in specialists, cause division of dentistry in â€œwomenâ€ and â€œmenâ€ specializations. The basis of the above-mentioned relation is common stereotypical opinions such as: Woman is more delicate, therapeutic dentistry does not demand heard work, there are needed thin and small fingers in dental therapy; Man is strong, smarter and calmer, he can risk and make a decision and so on. According to the results of this research, we can mention, that women dentists have stronger stereotypical opinions, than men dentists do. However, 100% of men dentists think, that dental surgeon must be a man and 100% of them think that it is better a man to be a head of clinic. Mostly men dentists work at full time jobs, they get married and have higher income then women dentists do. Most of the women dentists think that housework (husband, children) effects their professional growth. The gender stereotypes are widely spread and it has negative influence on both sex students and residents when choosing narrow specialties. General stereotypes that â€œcreateâ€ the social roles for men and women influence the working load of dentists; women dentists choose therapeutic and pediatric dentistry, hence they have less working hours and accordingly lower compensation.